Corporate-Startup Collaborative Innovation : New Models, Paths, and Approaches - Demir, Ferhat; Lukeš, Martin, 1976-; Špaček, Miroslav, 1954-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This dissertation, which consists of three articles and a unifying commentary, advances both theory and practical knowledge in Open Innovation (OI), with a particular focus on corporate-startup collaboration. The first article systematically identifies, organizes, and synthesizes the relevant literature on corporate-startup collaboration. The study contributes to the literature by identifying nine distinct collaboration models and categorizing them by equity ownership and startup stage. Additionally, it proposes a comprehensive framework with seven selection criteria (Corporate Strategy, Startup Stage, Equity Ownership, Innovation Maturity, Risks and Costs, Level of Integration, and Duration of Engagement) that managers can use to evaluate the different forms of collaboration and choose the most appropriate one (s). The second article explores corporate goals, activities, and outcomes in corporate–coworking collaboration by examining eleven cases of corporate engagement with coworking spaces. The study reveals that, based on their goals, corporates pursue different pathways to enhance their innovation capabilities, categorized as explorer, startup hunter, implementer, and transformer. This article concludes with two propositions: (1) Corporates enhance their innovation capabilities through collaboration with coworking spaces that host and orchestrate open innovation activities, resources, and actors, and (2) Corporates enhance their sensing, seizing, and transforming capabilities through collaboration with coworking spaces. The third article examines a novel mode of OI, termed “outside-out”, within multiple ecosystems centered around a corporate accelerator (CA). The study reveals how a CA constructs its ecosystem and orchestrates outside-out knowledge flows through five key mechanisms: co-designing, co-selecting, co-accelerating, co-investing, and reconciling.
It also identifies three distinctive practices of co-acceleration: startup matchmaking, business pivoting, and product validation. These mechanisms and practices enable the CA to effectively manage relationships among ecosystem partners and enhance the innovation outcomes of the incumbent firm and the broader ecosystem. By linking ecosystem literature with OI literature, the third study illustrates the influence of ecosystems on innovation outcomes and proposes a model for effectively orchestrating outside-out knowledge flows.
Vedoucí práce: Martin Lukeš
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management and managerial economics [obor disert. práce]; disertace; dissertations